The impact of insurance fraud detection systems - Jörg Schiller (Hamburg University, Institute for Risk and Insurance, 2002)
The purpose of this paper is to characterize the impact of fraud detection systems on the auditing procedure and the equilibrium insurance contract, when a policyholder can report a loss that never occurred. Insurers can only detect fraudulent claims through a costly audit (costly state verification). With fraud detection system insurers can depend their audit on the signal of the system and auditing becomes more effective. This paper presents conditions under which insurance fraud and the resulting welfare losses can be reduced by the implementation of a costly fraud detection system that is supplied by an external third party.
Keywords: D82; G22; 330; insurance fraud; auditing; detection system